Opportunities and Challenges of Implementing Federal Health System in Nepal at the Time of the COVID-19 Pandemic - Bhattarai, Sadikshya; Arjyal , Amit; Subedi, Madhusudan (Dhaulagiri Journal of Sociology and Anthropology, 2022)
Nepal has been practicing the federal system in health since the promulgation of the constitution in 2015. The new three-tier system of one federal, seven provincial and 753 local governments have set up ministries, departments, and health units at each level. Less than four years into this system, the country faced the COVID-19 pandemic. The pandemic created both opportunities and challenges for the federal health system. This study aims to identify those factors from the viewpoint of implementers of the health system. After an extensive literature review, exploratory qualitative research was carried out with twenty public health workers and elected representatives from all the tiers of government, including the federal ministry and governments of Lumbini Province. The data was analyzed using the R package for Qualitative Data Analysis (RQDA). Thematic analysis was performed using the World Health Organization’s six building blocks of the health system as an analytical framework. The participants highlighted many opportunities after federalization in Nepal. The presence of government closer to people helped to make policies and plans as per local needs. Decentralized power to make decisions at the local level made human and financial resources readily available to local governments leading to better service delivery at the time of need. In contrast, the challenges were difficulty transiting into the new system of governance, poor coordination among the different government tiers, and the lack of local expertise to manage and lead the health system during severe constraints posed by the global pandemic of an unprecedented nature. The study showed that the federalization in Nepal has met the goals of devolution of the power structure and better health system management. However, there are specific areas of improvement to ensure a more functional health system.